2008
DOI: 10.1016/j.mam.2008.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and neurocognitive dysfunction: Preventing “D”ecline?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
231
2
15

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 310 publications
(256 citation statements)
references
References 100 publications
8
231
2
15
Order By: Relevance
“…There is also emerging evidence of neuroprotective roles for vitamin D through antioxidant pathways, enhanced nerve conduction, neurotransmitter targets, neuronal calcium regulation, and effects on inflammation. 6,[10][11][12][13][14][15] Emerging data suggest that elevated levels of proinflammatory cytokines in the brain may be associated with depression. 15 In human studies, an inverse correlation was found between vitamin D status and inflammation markers, and a positive correlation was found with anti-inflammatory cytokines For personal use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also emerging evidence of neuroprotective roles for vitamin D through antioxidant pathways, enhanced nerve conduction, neurotransmitter targets, neuronal calcium regulation, and effects on inflammation. 6,[10][11][12][13][14][15] Emerging data suggest that elevated levels of proinflammatory cytokines in the brain may be associated with depression. 15 In human studies, an inverse correlation was found between vitamin D status and inflammation markers, and a positive correlation was found with anti-inflammatory cytokines For personal use.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 More recently, low vitamin D level has also been associated with neurologic disorders such as multiple sclerosis, Alzheimer disease, Parkinson disease, and cognitive decline. [3][4][5][6][7] Vitamin D receptors and the vitamin D-activating enzyme 1α−hydroxylase are found in most organ systems of the human body, including the brain. 8 Within the hypothalamus and the dopaminergic neurons of the substantia nigra is found a high density of vitamin D receptors as well as the vitamin D-activating enzyme.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a possible link between low vitamin D status and cognitive function is intriguing, especially in light of the projected increase in age-associated cognitive decline (Geda et al, 2008). Although much of the evidence base for this link has been from animal and in vitro studies (see reviews by Dawson-Hughes, 2008 andMcCann andAmes, 2008), a limited number of human studies have been conducted. For example, Przybelski and Binkley (2007) recently reported a significant positive correlation between serum 25(OH)D concentration and performance on the Mini-Mental State Examination (MMSE) in older adults; however, the sample size was small (n ¼ 32) and many had MMSE scores indicative of some degree of dementia.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Buell et al (2009) found a positive association between serum 25(OH)D and primary measures of executive functioning and attention processing speed in elderly adults. However, other data on the association between vitamin D status and cognitive function in humans are inconsistent (Jorde et al, 2006;Wilkins et al, 2006;McGrath et al, 2007;Slinin et al, 2010), possibly owing to the use of different cognitive batteries, some of which may have been inappropriate for the type of study/patient group (see review by Buell and Dawson-Hughes, 2008).…”
Section: Introductionmentioning
confidence: 99%